2022
DOI: 10.1155/2022/3744560
|View full text |Cite
|
Sign up to set email alerts
|

CircLATS2 Regulates miR-520a-3p/E2F7/p-VEGFR2 Signaling Pathway to Promote Hepatocellular Carcinoma Progression and Angiogenesis

Abstract: Objective. To investigate the effect of circLATS2 on the progression and angiogenesis of hepatocellular carcinoma and its molecular mechanism. Methods. The expression of circLATS2 in hepatocellular carcinoma was detected by qRT-PCR. The StarBase database was used to predict the potential miRNA, and the combination of the above was cytological verified by luciferase reporter gene assay and RNA pull down. The potential target genes of miRNA were predicted by TargetScan, verified by the above experiments, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Exploring the interaction between oncogenesis and the host immune system is important for discovering available effective prognostic biomarkers and therapeutic targets [ 40 , 41 ]. Previous studies have shown that a tumor immune microenvironment is shaped by immune infiltration status to a large extent [ 42 , 43 ]. In our study, we revealed the correlation between OSBPL3 expression and immune-cell infiltration status and immune purity in LIHC, providing novel insights into LIHC immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the interaction between oncogenesis and the host immune system is important for discovering available effective prognostic biomarkers and therapeutic targets [ 40 , 41 ]. Previous studies have shown that a tumor immune microenvironment is shaped by immune infiltration status to a large extent [ 42 , 43 ]. In our study, we revealed the correlation between OSBPL3 expression and immune-cell infiltration status and immune purity in LIHC, providing novel insights into LIHC immunotherapy.…”
Section: Discussionmentioning
confidence: 99%